Perancangan User Interface Sistem Informasi Kasir Berbasis Web di Zia Motor Subang (Current Research in Education: Conference Series Journal, 2023)
The industrial revolution 4.0 provides many changes in various fields of life, including the trade sector. Companies that utilize technology can have an influence on the development of the company, because it supports all process activities so that they can be more effective and efficient so that they can be more competitive in business competition. ZIA MOTOR Subang is a company that sells spare parts to variations and provides motorcycle repair services. However, one thing that is very unfortunate, as a workshop that is quite large and advanced, its business processes still use conventional manual methods, so they are considered less effective and efficient. Therefore, the purpose of this research is to be able to overcome the existing problems by making a user interface design in the development of a web-based cashier information system at this company using the design thinking method. So that with the development of this information system, it is hoped that it can help companies to save more time, energy and costs in managing stock data and conducting sales transactions so that they can be more neat, accurate and efficient so as to increase productivity and service at the company.